PEMAKNAAN BOLETA PADA TRADISI MASYARAKAT KELURAHAN MAREKU DI KOTA TIDORE KEPULAUAN - Mochammad Rizal Tri Putra; Suwito Suwito; Kasim Sinen (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2025)
Accounting practices are influenced by environmental factors such as economics, politics, culture, and demographics. While the influence of culture on social behavior has been extensively researched, the study of its impact on accounting practices is relatively new. Accounting, as a social science, develops through various paradigms and can adapt to the social, cultural, and religious environments in which it develops. In Mareku Village, Tidore Islands City, there is a boleta tradition that embodies social values such as mutual assistance and cooperation, and serves as a guide for community life. The aim of this research is to find out the perspective of the people of Mareku subdistrict in interpreting boleta. This research used a qualitative method with a phenomenological approach, with four informants who were directly involved in boleta activities. Data collection techniques using observation, interviews and documentation. The data testing technique uses triangulation. Based on the results of the analysis, three meanings can be found from the perspective of the Mareku sub-district community from boleta (donation) activities, namely; as a form of sincerity, as an effort to build brotherhood, and as a moral responsibility.